Co-integration analysis on all-variety Boro rice yields - Karmokar, Provash Kumar; Shitan, Mahendran (Academic Journals, 2011)
The Boro rice is one of the most important rice in Bangladesh. It has three varieties namely: high yielding, local and Pajam. The all-variety Boro rice yield of Rajshahi and Rangpur districts have been selected for the period from 1985 to 2007 to measure the relationship between them. Our study shows a cointegrating relationship exist between the yields. The speed of adjustment coefficient of the error correction model (ECM) for Rajshahi is 0.311. This indicates that there is about 31.1% of any deviation from the long-run path is corrected within a year by the yield of Rangpur. This ECM is adequate from the statistical view point.